2023
DOI: 10.1002/hpja.718
|View full text |Cite
|
Sign up to set email alerts
|

How healthy are Australian lunch box snacks with child‐directed marketing?

Abstract: Issue AddressedThe diets of Australian children, including their lunch boxes have a disproportionate amount of discretionary foods. Packaged snacks have marketing directed to both children and parents.MethodsPackaged school lunch box snacks were identified on supermarket websites. Nutrition information and child‐directed and parent‐directed marketing on the package were analysed. The “healthiness” of products was analysed using the Health Star Rating (HSR) (presently on packaging in Australia), two criteria de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Specifically, a systematic review of 28 international studies found socio-economic position was associated with predictors of dietary intake including home-environment factors, parent modelling and child nutrition knowledge ( Zarnowiecki et al , 2014 ). Furthermore, barriers to food provision influence families differently based on their situation, for example, a qualitative study with Australian mothers found that mothers who lacked time for preparation were less concerned about financial constraints, thus spending more on food ( Watson-Mackie et al , 2023 ). While parent/caregiver employment status, used as a proxy for time availability, was not significantly associated with cost when other demographics were controlled in the present study, the example from Watson-Mackie et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, a systematic review of 28 international studies found socio-economic position was associated with predictors of dietary intake including home-environment factors, parent modelling and child nutrition knowledge ( Zarnowiecki et al , 2014 ). Furthermore, barriers to food provision influence families differently based on their situation, for example, a qualitative study with Australian mothers found that mothers who lacked time for preparation were less concerned about financial constraints, thus spending more on food ( Watson-Mackie et al , 2023 ). While parent/caregiver employment status, used as a proxy for time availability, was not significantly associated with cost when other demographics were controlled in the present study, the example from Watson-Mackie et al .…”
Section: Discussionmentioning
confidence: 99%
“…Parent/caregiver employment status was used as a proxy to reflect parent/caregiver time availability, as being time poor is commonly identified as being a major limitation to preparing lunchbox foods. This relates to the findings from Watson-Mackie et al ., who found mothers who were not in the formal workforce had more time to prepare food that they considered healthy and avoid pre-packaged foods, in contrast with mothers working full-time ( Watson-Mackie et al , 2023 ). Additionally, international literature on both mothers and fathers demonstrates households with higher level of employment are more impacted by time barriers, contributing to convenience-based food choice coping strategies ( Devine et al , 2009 ; Wills et al , 2011 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations